SOSIAL SUPORT GURU BIMBINGAN DAN KONSELING UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR - Lopen, L Leonotus; Wibowo, Satrio Budi; Mudaim, Mudaim (Universitas Muhammadiyah Metro, 2023)
Learning discipline is an attitude or behavior to be able to carry out their obligations to learn, both studying at school and studying at home. The purpose of this study was